1976
DOI: 10.3109/00016487609107473
|View full text |Cite
|
Sign up to set email alerts
|

A topographic quantitative analysis of the Post-Natal bone formation in the auditory ossicles of the dog

Abstract: The amount and distribution of the post-natal bone deposition in the auditory ossicles and in the left tibia of dogs of varying ages were studied by means of alizarin labelling. The relative amount of fluorescent new-formed bone was expressed as a percentage ratio NB/(NB+PB) of new bone (NB) on the pre-existing bone (PB). The result was that the post-natal bone deposition (1) was larger in the tibia than in the incus, malleus and stapes; (2) significantly decreased with age both in the ossicles and in the tibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Rapid connective tissue restoration associated with simultaneous, active synthesis and breakdown of matricial collagen by osteogenic and fibrillogenic remodeling has been demonstrated in the oral tissues and many sutures (Ten Cate 1972, 1976, 1977. The stapes and otic capsule have been compared, and have shown similar remodeling activities as sutures of the skull vault containing essentially membrane bones (Anson et al 1948;Davies 1948;Anson and Davies 1980;Wright 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid connective tissue restoration associated with simultaneous, active synthesis and breakdown of matricial collagen by osteogenic and fibrillogenic remodeling has been demonstrated in the oral tissues and many sutures (Ten Cate 1972, 1976, 1977. The stapes and otic capsule have been compared, and have shown similar remodeling activities as sutures of the skull vault containing essentially membrane bones (Anson et al 1948;Davies 1948;Anson and Davies 1980;Wright 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Although both the human incudomalleal and incudostapedial synovial joints have been identified to be composed entirely of elastic tissue, while the SVJ is composed of fibrocartilage containing radially arranged medial and lateral fibrous bands, which are partly elastic and partly inelastic, attaching to the stapedial foot plate and chondroid wall of the oval window (Davies 1948;Harty 1953). On the other hand, comparative studies of the histology of the annular ligament have found that the joint of the kangaroo rat was connected solely with fine collagen fibers (Webster 1961 ing ear structure and function in mammals explained the disagreement by differences in the animal species used or in the methods employed (Engstrom 1947;Roberto 1976;Webster 1966). …”
Section: Discussionmentioning
confidence: 99%
“…The experiments were performed in the dog because the growth of its skeletal segments is similar to that of the primates (Godina, 1947). Moreover, the modelling processes have already been studied both in the external and inner canal and in the ossicular chain (Roberto, 1976;Roberto and Lozupone, 1987). The bone matrix laid-down after birth was easily identified using the well known technique of intravital staining of bone tissue with tetracycline.…”
Section: Introductionmentioning
confidence: 99%